Distribution of Endophytic Fungi in Leaves of Azadirachta indica A. JUSS. (Neem) of Panchmarhi Biosphere Reserve - Firoz Naem Khan2*, R.K. Tenguria1 and (Current Botany, 2011)
Total 85 endophytic fungi of 10 genera were isolated from 200 segments of fresh Azadirachta indica leaves collected from Panchmarhi biosphere reserve. The endophytic fungi recovered belong to hyphomycetes (68.2%), coelomycetes (19.99%), ascomycetes and sterile mycelium (5.88%) each. The most dominant endophytes observed were Trichoderma (21.17%), Pestalotiopsis spp. (16.47%) and Penicillium (15.29%).